The history boys [videorecording (DVD)] - Hytner, Nicholas; Anderson, Samuel, 1984-; Corden, James; Moore, Stephen Campbell; Bennett, Alan, 1934- (20th Century Fox Home Entertainment, 2007)
Centers around eight boisterous-yet-talented schoolboys hoping to gain admittance to England's most prestigious universities. They are aided on their quest by two teachers, a shrewd young upstart and an inspiring old eccentric, whose opposing philosophies challenge the boys to confront the true meaning of education and the relative values of happiness and success.